Odpowiedzi

2010-01-26T19:03:14+01:00
A.
4x - 3 = 3x + 5
4x - 3x = 5 + 3
x = 8

b.
5x + 2 = 7 - 3x
5x + 3x = 7 - 2
8x = 5 / 8
x = pięć ósmych

c.
3 (x - 1) = 0
3x - 3 = 0
3x = 3/3
x= 1

d.
-6 (x+1) = 24
-6x - 6 = 24
-6x = 24 +6
-6x = 30 / (-6)
x = -5

e.
-7 (x - 2) = 3x - 1
-7x + 14 = 3x - 1
-7x - 3x = -1 - 14
- 10x = -15 / (-10)
x = 3/2
x = 1,5

f.
4(x-1) = 6(1+x)
4x - 4= 6 + 6x
4x + 6x= 6 +4
10x= 10 /10
x=1
3 5 3
2010-01-26T19:03:27+01:00
A)
4x - 3 = 3x + 5
x = 8

b)
5x + 2 = 7 - 3x
8x = 5
x = 5/8 = 0.625

c)
3 (x - 1) = 0
3x - 3 = 0
3x = 3
x = 1

d)
-6 (x + 1) = 24
-6x - 6 = 24
-6x = 30
x = -5

e)
-7 (x - 2) = 3x - 1
-7x + 14 = 3x - 1
15 = 10x
x = 3/2 = 1.5

f)
4 (x - 1) = 6 (1 + x)
4x - 4 = 6 + 6x
-2x = 10
x = -5
3 4 3